Corruption in Public Service Delivery : An Experimental Analysis - Barr, Abigail; Lindelow, Magnus; Serneels, Pieter (2012)
To improve our understanding of corruption in service delivery, we use a newly designed game that allows us to investigate the effects of the institutional environment on the behavior of service providers and their monitors. We focus on the effect of four different factors: whether monitors are accountable to the service recipients, the degree of observability of service providers' effort, the providers' wages and the providers' professional norms. In accordance with theory, we find that service providers perform better when monitors are elected by service recipients and when their effort is more easily observed. However, there is only weak evidence that service providers perform better when paid more. Monitors are more vigilant when elected and when service providers are paid more. Playing the game with Ethiopian nursing students, we also find that those with greater exposure to the Ethiopian public health sector perform less well, either as provider or as monitor, when the experiment is framed as a public health provision scenario, suggesting that experience and norms affect behavior.